Synthesis of Morpholine Containing Sulfonamides: Introduction of Morpholine Moiety on Amine Functional Group. Issue 3 (2004) - Singh, D.; Bansal, G.
Abstract : Sulfonamides have been the center of drug structures as this group is quite stable & well tolerated in human beings. The synthesis of these structures was started in search of new pharmacological active reagents. These compounds are being tested for the desired activity (ICAM-1/LFA-1 Interaction inhibitors as anti-adhesion therapeutic agents), the biological activity & structure activity relationship will be published elsewhere. Synthesis of morpholine moiety from amino group is done by using reagent 2-chloroethanol.